Music Mood Player Implementation Applied In Daycare Using Self Organizing Map Method - Dewi, Kadek Cahya; Putri, Luh Arida Ayu Rahning (Jurnal Buana Informatika, 2011)
Abstrak. Implementasi Music Mood Player Yang Diaplikasikan Pada Daycare Menggunakan Metode Self Organizing Map. Musik adalah seni, hiburan dan aktivitas manusia yang melibatkan suara-suara yang teratur. Musik berkaitan erat dengan psikologi manusia. Sepotong musik sering dikaitkan dengan kata sifat tertentu seperti senang, sedih, romantis, dsb. Keterkaitan antara musik dengan mood tertentu ini telah banyak digunakan dalam berbagai kesempatan oleh manusia, untuk itu klasifikasi musik berdasarkan keterkaitannya dengan emosi tertentu menjadi penting. Daycare merupakan salah satu lembaga yang memanfaatkan musik sebagai terapi atau sarana pendukung dalam kegiatan pengasuhan anak. Penelitian ini fokus pada implementasi music mood player menggunakan Self Organizing Map yang diaplikasikan pada Daycare. Fitur yang digunakan sebagai ciri adalah rhythm pattern dari musik tersebut. Parameter mood didapatkan dari Robert Thayerâs energy-stress model yang terdiri dari exuberance / gembira, contentment / rilex, anxious / cemas dan depression. Sistem diuji dengan lagu dari berbagai genre dan mood hasil klasifikasi dibandingkan dengan mood dari pakar psikologi anak. Mood lagu dari sistem dapat diset secara otomatis disesuaikan dengan aktivitas pada daycare.Â Kata Kunci: Music Information Retrieval, Klasifikasi Mood, Klasifikasi Musik, Self Organizing Map, Rhythm Patterns.Â Abstract. Music is an art, entertainment and human activity that involve some organized sounds. Music is closely related to human psychology. A piece of music often associated with certain adjectives such as happy, sad, romantic and many more. The linkage between the music with a certain mood has been widely used in various occasions by people, there for music classification based on relevance to a particular emotion is important. Daycare is one example of an institution that used music as therapy or tools of support in each of its parenting activities. This research concerns in implementation of a music mood player using Self Organizing Map applied at the Daycare. The features that are used on this music mood player are rhythm patterns of the music. The mood parameters that used in this system is based on Robert Thayers energy-stress model which are exuberance / happy, contentment / relax, anxious and depression. The system is tested using a set of songs with various genres and the classification results are compared with the mood obtained by child psychology expert. The system can be set automatically according to the activities at daycare.Â Keywords: Music Information Retrieval, Mood Classification, Music Classification, Self Organizing Map, Rhythm Patterns.